2015
DOI: 10.1007/s12035-015-9656-6
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Enrichment Prevent the Juvenile Hypoxia-Induced Developmental Loss of Parvalbumin-Immunoreactive Cells in the Prefrontal Cortex and Neurobehavioral Alterations Through Inhibition of NADPH Oxidase-2-Derived Oxidative Stress

Abstract: We compared the expression of phenotype of parvalbumin (PV)-immunoreactive cells in the prefrontal cortex (PFC) of juvenile rats reared in enriched environment (EE) after daily intermittent hypoxia (IH) exposure to those reared in standard environment (SE) and investigated the involvement of NADPH oxidase-2 (NOX2)-derived oxidative stress in the IH-induced neurodevelopmental and neurobehavioral consequences in a juvenile rat model of obstructive sleep apnea. Postnatal day 21 (P21) rats were exposed to IH or ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 42 publications
1
16
0
Order By: Relevance
“…Additionally, we recently found (Yang et al, 2016) that ROS are essential for the sensitization of capsaicinsensitive vagal afferents and the development of lower airway hyperreactivity induced by 14 days IH. The activation of NADPH oxidase is known to be a major source of ROS in various tissues in response to IH (Peng et al, 2009;Williams et al, 2015;Zhang et al, 2016;Liu et al, 2019). Indeed, the increased levels of lipid peroxidation in laryngeal tissues observed in this study were totally inhibited by apocynin, suggesting that ROS may be derived from the activation of NADPH oxidase.…”
Section: Discussionsupporting
confidence: 45%
“…Additionally, we recently found (Yang et al, 2016) that ROS are essential for the sensitization of capsaicinsensitive vagal afferents and the development of lower airway hyperreactivity induced by 14 days IH. The activation of NADPH oxidase is known to be a major source of ROS in various tissues in response to IH (Peng et al, 2009;Williams et al, 2015;Zhang et al, 2016;Liu et al, 2019). Indeed, the increased levels of lipid peroxidation in laryngeal tissues observed in this study were totally inhibited by apocynin, suggesting that ROS may be derived from the activation of NADPH oxidase.…”
Section: Discussionsupporting
confidence: 45%
“…Abnormal production of NOX2-derived ROS occurs not only in neurodegenerative diseases and ischemic conditions, but also in psychiatric disorders [53]. Zhang et al [54] showed that EE attenuates NOX2-derived oxidative stress induced by daily intermittent hypoxia exposure. The above finding in conjunction with our results indicates that positively stimulating environments may reduce the expression of NOX and, thus, a lower level of ROS production leading to less damage to ROS-sensitive proteins.…”
Section: Discussionmentioning
confidence: 99%
“…In the mouse model, PFC damage induced by hypoxic conditions including ghost cells, increased the neuronal death and upregulated the expression of molecules such as VEGF, Glut1, Hif-1, and lactate dehydrogenase A, which might cause a local excitability in PFC neurons [ 81 , 87 ]. In addition, NADPH oxidase-2 induced the oxidative stress that might contribute to the developmental loss of parvalbumin- (PV-) positive cells (PV-cells) in the PFC and progression of psychiatric anxiety in rat models [ 72 , 88 ]. Moreover, the loss of PV-cells in the PFC and the IH-induced psychiatric anxiety can be alleviated by inhibiting the NADPH oxidase-2-induced oxidative stress [ 88 ].…”
Section: Hypoxic Injury and Neuronal Plasticitymentioning
confidence: 99%
“…In addition, NADPH oxidase-2 induced the oxidative stress that might contribute to the developmental loss of parvalbumin- (PV-) positive cells (PV-cells) in the PFC and progression of psychiatric anxiety in rat models [ 72 , 88 ]. Moreover, the loss of PV-cells in the PFC and the IH-induced psychiatric anxiety can be alleviated by inhibiting the NADPH oxidase-2-induced oxidative stress [ 88 ].…”
Section: Hypoxic Injury and Neuronal Plasticitymentioning
confidence: 99%